Analytical Study of the Causes of Abandoned Construction Projects - Abdullah Adil; Tariq Abdulmajid; Samiaah Mahdi (Salehan Institute of Higher Education, 2019)
Construction industry is a vital field as it plays a significant role in the economic situation of the country. Many job opportunities will be created to develop and enhance the economy. However, not all projects can be finished on time or ahead of schedule, as the project may be delayed or even abandoned in worst cases at any stage of the project's cycle lifetime. Project abandonment is a serious problem which impedes the construction industry in many countries especially in Middle East. This paper is part of an ongoing research investigation to identify the most significant causes of project abandonments in Iraq. It presents a review of an existing literature on the causes of this problem. Consequently, the outcome of an extensive questionnaire survey of 40 crucial causes including 101 respondents is presented and discussed. Various statistical tools were used in the analysis of data such as descriptive statistics, Cronbach's alpha, and relative important index (RII) with the aid of SPSS and MS Excel. The result illustrates that the most significant and vital causes in Iraq were: Financial corruption, Assignment of work to companies that have no experience in that field, and Incompetent Contractor. The findings of this study will help future researchers looking for solutions for this problem in order to enhance the project success.